Multilayers of avidin–biotin complexes as spacers used in the study of the effect of metal‐enhanced fluorescence. Issue 6 (3rd June 2022) - Cai, You‐Ru; Liu, Yi‐Ting; Luo, Xue‐Feng; Lee, Yin‐Yu; Tan, Kui‐Thong; Chen, I‐Chia
Abstract: The effects of metal‐enhanced fluorescence (MEF) of rhodamine dye by gold sub‐micro hexagonal plates were studied. A multilayered avidin–biotin complex was designed and used as a spacer to connect the fluorophore and the sub‐microplate. Fluorescence lifetime image microscopy (FLIM) combined with time‐correlated single‐photon counting was used to obtain lifetime images and intensities of dye on single particles. Gold hexagon plates 900 nm were synthesized, and the avidin–biotin complexes were placed layer‐by‐layer for up to 4 layers onto the sub‐microplates. All emission curves of fluorophore displayed biexponential decay with short lifetimes of 18–23 ps and long lifetimes of 249, 271, 304, and 348 ps for 1–4 layers on gold sub‐microplates, respectively. Using the kinetic model of energy transfer between fluorophore and nanoparticles to explain the coupling mechanism, we found that the excited fluorophore transferred energy mostly to the high‐order modes for the 1‐layered avidin–biotin complexes enclosing gold nanospheres, consequently resulting in a non‐emissive pathway. The 4‐layered samples had the highest emission intensity because, at those distances, the enhancement by the gold sub‐microplates during plasmonic excitation remained high and became comparable to the energy quenching rate. Using the composed complexes, the MEF effect achieved the maximal enhancement in this system. Abstract : Multilayer avidin‐biotin complex system with biological compatibility was used as a spacer for metal‐enhanced fluorescence applications. Four layered avidin‐biotin samples yielded the best MEF effect.